PENGARUH PEMBERIAN AROMA TERAPI LAVENDER TERHADAP PENURUNAN NYERI HAID PADA MAHASISWI DI STIKES HUSADA JOMBANG - Maabuat, Embriani; Sasmito, Nanang Bagus; Zatihulwani, Eliza Zihni (PRIMA WIYATA HEALTH, 2025)
Background: Dysmenorrhea is pain caused by contractions of the abdominal muscles that occur continuously when bleeding. Objectives: The purpose of this study was to determine the effect of lavender aromatherapy on reducing the intensity of menstrual pain in female students at STIKes Husada Jombang. Methods: The research design is experimental analysis. The population in this study were all female students at STIKes Husada Jombang with the One Group Pretest Posttest technique with a total sample of 34 respondents. Data collection used SOP sheets, and checklist sheets and data analysis used the dependent t-test. Results: The results showed that before giving lavender aromatherapy most of the respondents had moderate menstrual pain as many as 18 respondents (52.9%) and after giving lavender aromatherapy most of the respondents who had no pain were 18 respondents (52.9%). The test results are reinforced by the results of the difference through the statistical test value of the dependent T test obtained a significant number or probability value of 0.000. The p-value of this study shows that if the p-value <α (0.05) then H1 is accepted, which means that lavender aromatherapy has an effect on menstrual pain in respondents. Conclusion: Based on the description above, there is an effect of lavender aromatherapy on reducing menstrual pain in STIKes Husada Jombang students. This aromatherapy provides a calming and relaxing effect on the body so that it can reduce the intensity of pain felt by a person, according to what was said by the respondent after giving the therapy the respondent felt calmer, relaxed, comfortable, and pain he felt began to decrease after giving relaxation with aromatherapy.